Delivering Fitness : Your Guide to Health and Strength Training during Pregnancy. - Quatro, Christine (Electronic & Database Publishing Inc., 2004)
This book is a concise, easy-to-read guide to fitness and nutrition during pregnancy that explains the importance of exercise and proper eating without being intimidating to a newly pregnant woman. The authors have devised a unique fitness program incorporating key strength-training exercises specifically designed for each trimester and for the postpartum period.